Reviews (Blackfriars, 1935)
The Well and the Shallows. By G. K. Chesterton. The Destructive Element. By Stephen Spender. Work and Leisure. By Eric Gill. Les Droits du Travailleur et le Corporatisme. By P. Chanson. Principles of Biology. By G. Waddington, S.J. Joc and Colette at the Natural History Museum. By Vera Barclay. English Wild Animals. By J. Fairfax-Blake-borough. A History of Europe. Saint Peter Canisius, S.J. The Catholic Revival in Italy 1815–1915. Mediæval Studies